Clinical Profile in Refractory Heart Failure and Its Outcome in Rural Institutional Setup - Godhiwala, Parth; Acharya, Sourya; Kumar, Sunil (International Journal of Psychosocial Rehabilitation, 2020)
Refractory HF can be defined as “the persistence of symptoms that limit daily life (functional class III or IV of the New York Heart Association [NYHA]) despite optimal previous treatment with drugs of proven efficacy for the condition.” This is very challenging to manage and so disease is associated with poor quality of life and high mortality rates. This study has been planned to see the clinical profile like etiology, clinical features and prognosis as studies regarding this in India is lacking.To study clinical profile of refractory heart failure in rural tertiary care hospital.To identify aetiology of refractory heart failure in rural population.To study the outcomes as duration of ICU stay, discharge and death.To compare the outcome in different gender and Body mass index status.In this cross sectional study, 40 patient were enrolled and diagnosed on the basis of criteria for refractory HF (European Society of Cardiology). Patient were admitted in Medicine department from October 2018 to January 2020.20(50%) patients had coronary artery disease, 18(45%) patients had cardiomyopathy, 22(55%) patients had acute or history of myocardial infarction. 6MWT was done in all patients (excluding patients who had contraindications). Total of 14(35%) patients had